Funding Black High‐Growth Startups - COOK, LISA D.; MARX, MATT; YIMFOR, EMMANUEL (Journal of Finance, 2026)
ABSTRACT We classify the race of over 160,000 U.S. founders and investors and study the venture capital (VC) funding gap for Black entrepreneurs. Only 3.1% of VC‐funded startups are Black‐owned, and they raise half as much VC funding as others. We attribute much of this gap to Black founders having fewer traditional success markers, like patents or entrepreneurial experience. This disparity also affects matching: Black VC partners invest more in Black founders, and these investments have higher successful exit rates. We attribute this outperformance to lower information asymmetries due to network overlap and “screening discrimination,” whereby Black VCs better differentiate among Black founders.